Propagasi in vitro tanaman kurma (Phoenix dactylifera L.) pada bioreaktor dengan perendaman sesaat - Rizka Tamania SAPTARI; Masna Maya SINTA; Imron RIYADI; . PRIYONO; . SUMARYONO (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2020)
The cultivation of date palm in Indonesia has increased since the last decade. However, the superior date palm seedlings are still limited and most of them are imported from other countries. The mass supply of superior date palm seedlings can be provided by in vitro propagation in the bioreactor. Therefore, the research was conducted to develop a protocol of date palm in vitro propagation by using Temporary Immersion Bioreactor (TIB). The in vitro propagation was carried out through somatic embryogenesis technique using meristematic tissues isolated from offshoots of date palm female clone cv. Zambli as explants. The explants were sterilized and then cultured to produce embryogenic calli and somatic embryos. Afterwards, somatic embryos germination and plantlets formation were conducted in TIB with treatments of immersion period: 3, 10, and 30 minutes every 6 hours, with 8 replications, The results showed that the optimal somatic embryo germination in TIB was with the immersion period of 30 min every 6 h, resulting in the most formation of shoots and fresh biomass weight increment up to nearly threefold in 6 weeks. Thereafter, plantlets formation in TIB with immersion period of 10 min and 30 min every 6 h exhibited similar performances in producing more plantlets with higher total fresh weight and better vigor than those of 3 min every 6 h. However, there were more rooted plantlets in the TIB with immersion period of 10 min every 6 h. Based on the results, an in vitro propagation protocol via somatic embryogenesis in TIB has been successfully developed for mass propagation of date palm cv. Zambli, which produced plantlets with good vigor and rooting.